2004
DOI: 10.1016/s0074-7696(04)35004-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Surface Peptidases

Abstract: The cell surface has various functions: communicating with other cells, integrating into the tissue, and interacting with the extracellular matrix. Proteases play a key role in these processes. This review focuses on cell-surface peptidases (ectopeptidases, oligopeptidases) that are involved in the inactivation or activation of extracellular regulatory peptides, hormones, paracrine peptides, cytokines, and neuropeptides. The nomenclature of cell-surface peptidases is explained in relation to other proteases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 190 publications
(173 reference statements)
4
60
0
2
Order By: Relevance
“…DPP-IV is a pleiotropic enzyme that cleaves, and thereby generally inactivates, a variety of peptide hormones, neuropeptides and chemokines (reviewed in [16,17]). Furthermore, it acts as a binding protein for fibronectin and adenosine deaminase, and is a co-stimulator of T-cell activation.…”
Section: Potential Risks Associated With Dpp-iv Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPP-IV is a pleiotropic enzyme that cleaves, and thereby generally inactivates, a variety of peptide hormones, neuropeptides and chemokines (reviewed in [16,17]). Furthermore, it acts as a binding protein for fibronectin and adenosine deaminase, and is a co-stimulator of T-cell activation.…”
Section: Potential Risks Associated With Dpp-iv Inhibitorsmentioning
confidence: 99%
“…Potential side-effects resulting from the prolongation of action of these messengers include neurogenic inflammation (substance P, neuropeptide Y), increases in blood pressure (neuropeptide Y), enhanced general inflammation, and allergic reactions (chemokines). However, to date, such side-effects have not been observed in preclinical animal or clinical human studies [17].…”
Section: Potential Risks Associated With Dpp-iv Inhibitorsmentioning
confidence: 99%
“…DPP4 (DPP4/DPPIV/CD26) is a 110-kDa type integral membrane glycoprotein that cleaves N-terminal dipeptides from peptides with preferably proline or alanine at the penultimate 62) . Interestingly, these substrates are bioactive peptides that regulate the cardiovascular system 63,64) (Fig.…”
Section: Dpp4 Inhibition In Heart Failure: Friend or Foe?mentioning
confidence: 99%
“…7 Furthermore, it has been suggested that cell surface peptidases play an important role in the activation or inactivation of mediators involved in the occurrence and perpetuance of inflammatory processes. 8 Dipeptidyl peptidase IV (DPP IV; EC 3.4.14.5), known as CD26 molecule is a widely expressed multifunctional glycoprotein present both on the cell surface of various tissues and as a soluble form in plasma and other biological fluids. As a serine protease, DPP IV cleaves the N-terminal dipeptides from proteins having either proline or alanine at the penultimate position.…”
Section: Introductionmentioning
confidence: 99%